Analysis of Mathematical Connection Ability of PGSD Undergraduate Students for Geometric Shapes Content - Deti Rostika; Prihantini; Komariah (International Conference on Elementary Education, 2023)
Mathematics is a science that provides the ability to think logically and mathematically. The ability to think logically and mathematically is reflected in mathematical connection. Students of Elementary School Teacher Education Program (S1 PGSD) are prospective teachers who will teach mathematics in elementary schools, and will have the obligation to provide students with mathematical connection ability. Therefore, undergraduate students of S1 PGSD need to have mathematical connection ability as basic skills for teaching mathematics. This study aims to analyze the mathematical connection abilities of PGSD undergraduate students for Geometric Shapes content. The research questions are as follows: (1) what is the mathematical connection ability possessed by PGSD undergraduate students for geometric shapes content, (2) what mathematical connection skills are still low in PGSD undergraduate students for geometric shapes content, (3) what mathematical connection skills do PGSD undergraduate students already have at high category for geometric shapes content. The study applied a quantitative descriptive method, with the research subjects totaling 30 students of fourth semester who were taking Geometry and Measurement courses. Data collection techniques using multiple choice tests totaling 30 items. The conclusion is that the average mathematical connection ability of S1 PGSD students reached 62.49% in the sufficient category. The mathematical connection ability which shows is still low is the indicator of mathematical connection ability with other fields/sciences is 40.00%, and the ability shows high category is connection ability between topics in mathematics.